Labor Education for Women Workers - Wertheimer, Barbara Mayer (Temple University Press, 2018)
Labor Education for Women Workers was published in 1981, a year that marked a significant shift in labor-movement history. This essential text raised awareness of the importance of creating space for women workers to have solid labor education and filled a major gap in the literature on labor education with an accessible yet scholarly guide. This happened to be the first year of Ronald Reagan's first term as president. His administration broke the Professional Air Traffic Controllers Organization strike and signaled the beginnings of an ensuing backlash against progressive social movements and a shift towards regressive policies, forcing the labor movement to go on the defensive. Similar to 1981, Labor Education's reissue comes during yet another a tumultuous shift in the nation's landscape. Following the election of Donald Trump, on Inauguration Day, women of color called for and led the largest global women's march in history. Just before the U.S. Supreme Court heard oral arguments in the Janus v. American Federation of State, Municipal, and County Employees case, women workers and trade unionists took to the streets for the National Working People's Day of Action to protest a ruling that would severely restrict the ability of public-sector unions to collect dues from union members. Needless to say, when more than half of the states have Right to Work laws, the labor movement is still in a defensive position. New generations bring about new forms of resistance and organizing, but there is no substitute for coming together in women-only spaces to share expertise and challenges and to strategize targeted methods for improving worker-justice organizations and the world of work for women. Barbara Wertheimer provided us with a foundational that can support and sustain the resistance in this moment.